Mental health knowledge and classroom experiences of school teachers in Aragon, Spain - Granada-López, José Manuel; Ramón-Arbués, Enrique; Echániz-Serrano, Emmanuel; Juárez-Vela, Raúl; Cobos-Rincón, Ana; Satústegui-Dordá, Pedro José; Navas-Echazarreta, Noelia; Santolalla-Arnedo, Iván; Nash, Michael (Frontiers in Public Health, 2023)
Background Research shows that many mental disorders begin in childhood but are sometimes not diagnosed until later years. School-age children spend much of their time in schools and have daily interactions with school teachers. Aim Examine school teachers’ experiences of mental disorders in school going children and adolescents and their associated mental health training needs. Method and sample A descriptive cross-sectional study was carried out with teachers in Infant-Primary and Secondary Education-Baccalaureate schools. Results A convenience sample of 685 teachers responded to the online survey. Participants worked in both urban and rural areas and in Infant-Primary and Secondary Education-Baccalaureate schools. Over half of participants reported classroom experiences of learner mental disorders such as ADHD, anxiety, conduct disorders or autism. Most participants acknowledged a training need, both in recognition of symptoms of mental disorders and in care resources and processes. However, 80% of respondents reported having not received any training in this regard. Participant preferences for training included face-to-face or hybrid – combined online learning. Participants also considered the management of their own mental health to be deficient, therefore any training should incorporate personal mental health awareness and self-help strategies. Conclusion In Aragón (Spain), teachers of children and adolescents with mental disorders, recognize a need for training in the identification of symptoms and other aspects of mental healthcare, such as availability and access to services. Protocols for early identification and referral would promote mentally healthy school environments and reduce stigma which could be a barrier to timely intervention. In addition, any training should include mental health self-care for teachers.